Youtube Creative Content As A Source Of Income From Islamic Business Ethics - Achmad Zulfikar Siregar; Mhd Amalan Pasaribu; Nurlaily Kamilah Daulay; Purnama Wahyuni MS (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2022)
The increasingly fierce business competition, especially at the global Revised  level, not only requires business actors to always be vigilant and Accepted  creative, but also has an unfavorable impact on the environment and human benefit. This phenomenon implicates the many actions of business people tend to ignore the principles of business ethics. This study aims to discover how YouTube creative content is used as a source of income by Youtubers Community from Indonesia  and to find out its accordance with Islamic business ethics. The subjects in this research are Indonesia YouTubers whose Youtube channels have been monetized and have more than 100,000 subscribers. Data was collected through observation and documentation. Data was analysed using qualitative analysis by describing events and relating them to Islamic business ethics. The results of the study found that there are some YouTubers who ignore some principles of business ethics in Islam by posting negative content (obscenities, vulgar videos, and pranks), namely: Jess No Limit, Frost Diamond, namely: Ricis Official, Atta Halilintar, Rans Entertaiment, Baim Paula, GEN HALILINTAR.